Non -destructive measurement of citrus internal quality using near infrared spectroscopy and x-ray computed temography - Lebotsa, Phalane Sekina (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScEng)--Stellenbosch University, 2017.